2016
DOI: 10.1016/j.pneurobio.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s disease due to loss of function: A new synthesis of the available data

Abstract: Alzheimer's Disease (AD) is a highly complex disease involving a broad range of clinical, cellular, and biochemical manifestations that are currently not understood in combination. This has led to many views of AD, e.g. the amyloid, tau, presenilin, oxidative stress, and metal hypotheses. The amyloid hypothesis has dominated the field with its assumption that buildup of pathogenic β-amyloid (Aβ) peptide causes disease. This paradigm has been criticized, yet most data suggest that Aβ plays a key role in the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
112
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(116 citation statements)
references
References 413 publications
(158 reference statements)
3
112
0
1
Order By: Relevance
“…A study showed that only free curcumin could reduce amyloid plaque burden and insoluble β‐amyloid peptide (Begum et al, ). Research included participants in a stage of dementia characterized by loss of neurons and senile plaque deposits outside neurons (Kepp, ). However, significant plasma levels of native curcumin, which prevents or reverses half the aggregation (IC50) of Aβ after 2‐ and 4‐g/day curcumin C3 complex (Ringman et al, ), could not be measured.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that only free curcumin could reduce amyloid plaque burden and insoluble β‐amyloid peptide (Begum et al, ). Research included participants in a stage of dementia characterized by loss of neurons and senile plaque deposits outside neurons (Kepp, ). However, significant plasma levels of native curcumin, which prevents or reverses half the aggregation (IC50) of Aβ after 2‐ and 4‐g/day curcumin C3 complex (Ringman et al, ), could not be measured.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence exists that native Aβ, which is produced during neuronal activity (Cirrito et al ., 2005), may subserve physiological functions (reviewed in Giuffrida et al ., 2010; Kepp, 2016). In particular, endogenous Aβ seems to be relevant for the control of synaptic activity and memory formation (Puzzo et al ., 2011; Piccini et al ., 2012), via the activation of α‐7‐nAChRs (Calabrese, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to copper ions, some propose that AD is a disease of dietary copper deficiency (Klevay, 2008), while others propose it is caused by excess inorganic copper in the diet that can be treated using zinc therapy (Hoogenraad, 2011; Brewer, 2014) or a low-copper diet (Squitti et al, 2014b). Soluble, monomeric Aβ 1−x has even been proposed to possess a normal function in metal export, whereby metal-enrichment within plaques is associated with a loss of function (Kepp, 2016). Other potential physiological functions of Aβ 1−40/42 have been proposed, as an antimicrobial peptide (Soscia et al, 2010; Kumar et al, 2016) and as a cerebrovascular sealant (Atwood et al, 2003), although any role for copper ions in these contexts remains to be established.…”
Section: Introductionmentioning
confidence: 99%